Interaction between Venture Capitalists' Screening Criteria and their Individual Bias - A Part of the East Midlands Early Growth Fund Project - Mu, Jasmine Chao-wen (2007)
Venture capitalists (VCs) usually utilize a bundle of selection criteria in identifying a potential venture among hundreds of business plans they receive every year. These guidelines primarily cover four major categories: management, product, market and financials. Management, including entrepreneurs and venture team, are the most frequently indicated factor to be critical to the success of a new company. The key points related to these criteria from various literatures are summarized in this study. Meanwhile, this report is to seek the factors offsetting the effect of these criteria and making VCs invest in a company with no return. VC firms'strategies and VCs'own personal biases, experience limitations, peer and market pressures, and rough communication skills would be the major blame to some irrational behaviour, leading to a wrong choosing or miss a good opportunity. Through interviewing twelve ventures which are screened from the internship project for the East Midlands Early Growth Fund, this study used the viewpoints from ventures to scrutiny VCs' behaviour. The research method starting from the ventures' points is proved in this study to be more effective than the traditional one taking off from the VC side. The findings showed that VCs did behave unprofessionally sometimes. Additional discoveries came out that some quality companies would request for value-added benefits other than capital from VCs, while VCs may lose them because these ventures' invisibility to VCs. Meanwhile, quite a few of decision aid models can assist VCs in avoiding the biased judgement, although the VCs' introspection and experiences are still the key to their correct decisions. Ventures can also acquire inspiration from this study. Some relevant topics are raised at the end for future researches.